Tanggung Jawab Penyelenggara Penerbangan Charter - Khristyawan Wisnu Wardana (Fakultas Hukum Universitas Mulawarman, 2006)
Looked from geographical sides, wide of teritory and spreading of resident, the function and role of air transport in Indonesia have very goodness strategic position reviewed from national unity, social cultural, economics, governance and also security and defence things. The raise request of air transport service by consumer must be balance with management transportation system to fulfill all consumer demand inwroughtly. In line with the raising of air transport service, charter air transport companys getting raise too. Aviation activity especially conducted by air transport companys is katastrofis, it means that if is in the event of accident can generate very big loss of human being and financial. Beside loss to its plane, also loss to passenger, baggage even to hit third party. In that kind of situation, air transport companys cannot discharge of it responsibility to any loss during the aviation. Key words: penyelenggara penerbangan charter (charter air transport companys), tanggung jawab (responsibility).